Maldives Development Update, April 2021 : A Digital Dawn - World Bank (World Bank, Washington, DC, 2021)
The Coronavirus (COVID-19) pandemic brought global tourism and travel to a standstill. Thus, although the health impact of the pandemic has been fairly contained in Maldives, its economic consequences have been devastating. To contain the spread of the virus, the country closed its borders for the first time in history, between March 27 and July 15, 2020, leading to a sudden stop in tourism, the main driver of growth, jobs, and revenues. The special focus article of the April 2021 Maldives Development Update explores how Maldives can leverage digital technologies to build back better for green, resilient, and inclusive development in the post-COVID world. It identifies the main bottlenecks to greater digital adoption and provides preliminary recommendations on how the government can address them.